Antimicrobial Activity of Several Cineole-Rich Western Australian Eucalyptus Essential Oils - Fahad S. Aldoghaim; Gavin R. Flematti; Katherine A. Hammer (Microorganisms, 2018)
Essential oils from the Western Australian (WA) Eucalyptus mallee species Eucalyptus loxophleba, Eucalyptus polybractea, and Eucalyptus kochii subsp. plenissima and subsp. borealis were hydrodistilled from the leaves and then analysed by gas chromatography⁻mass spectrometry in addition to a commercial Eucalyptus globulus oil and 1,8-cineole. The main component of all oils was 1,8-cineole at 97.32% for E. kochii subsp. borealis, 96.55% for E. kochii subsp. plenissima, 82.95% for E. polybractea, 78.78% for E. loxophleba 2, 77.02% for E. globulus, and 66.93% for E. loxophleba 1. The Eucalyptus oils exhibited variable antimicrobial activity determined by broth microdilution, with E. globulus and E. polybractea oils showing the highest activities. The majority of microorganisms were inhibited or killed at concentrations ranging from 0.25% to 8.0% (v/v). Enterococcus faecalis and Candida albicans were the least susceptible organisms, whilst Acinetobacter baumannii was the most sensitive. In conclusion, all oils from WA Eucalyptus species showed microorganism inhibitory activity, although this varied according to both the Eucalyptus species and the microorganism tested. These data demonstrate that WA Eucalyptus oils show activity against a range of medically important pathogens and therefore have potential as antimicrobial agents.